Librarians’ behavioral performance on chat reference service in academic libraries: Perceived importance vs actual practices - Mohd Azmi, Nor Azilawati; Noorhidawati, A.; Yanti Idaya Aspura, M.K. (Malaysian Journal of Library and Information Science, 2017)
This study reports a comparison study between perceived importance and actual practice of guidelines for chat reference service among academic librarians. Behavioral Performance of Reference and Information Service published by the Reference and User Service Association (RUSA) was used in the development of the survey instrument. The study employed a quantitative approach to address the following research objectives: i) to determine academic librarians’ perceived importance and current practices of behavioral performance in the interaction during the chat reference service; and ii) to assess the association between academic librarians’ perceived importance and actual practices of behavioral performance in the interaction during the chat reference service. A survey was administered to 92 librarians from six academic libraries in Malaysia which providing chat reference service to their users. A response rate of 84.8 percent was achieved resulting in 78 usable questionnaires to be analysed. The finding in general demonstrates majority of the respondents rated their perceived importance higher than actual practices. The mean gap difference between perceived importants of RUSA guideline and the level of practices among librarians is beneficial to identify areas in chat reference services that need improvement. The finding could provide an empirical benchmark for evaluating chat reference services.